2021
DOI: 10.3390/su132111828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SME’s Managerial Ability and Executive Compensation on Firm Value

Abstract: This paper analyzes the impact of the managerial ability and level of compensation on firm value in small and medium enterprises. The ability of managers is important for the sustainability and growth of small and medium enterprises because they lack awareness of resources, technology, and reputation compared to large enterprises. The managerial ability is the ability to efficiently utilize resources and choose the investment plan with the highest future net cash flows. Managerial ability is also an indicator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In the work of [15], it is mentioned that the estimation of the volumes of waste and emissions is necessary for the effectiveness in the adoption of CP because there are many managers that are unaware of the opportunities to achieve financial gains from the adoption of CP. The studies of [10,30] contributed to this argument by referring to the opportunity of achieving economic gains from the implementation of CP. However according to [37], CP is not thoroughly known in terms of cost-benefit analysis, and that most companies does not make a viable comparison between the environmental investments focused on the end line and the investments related with CP.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work of [15], it is mentioned that the estimation of the volumes of waste and emissions is necessary for the effectiveness in the adoption of CP because there are many managers that are unaware of the opportunities to achieve financial gains from the adoption of CP. The studies of [10,30] contributed to this argument by referring to the opportunity of achieving economic gains from the implementation of CP. However according to [37], CP is not thoroughly known in terms of cost-benefit analysis, and that most companies does not make a viable comparison between the environmental investments focused on the end line and the investments related with CP.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
“…CP practices are attributed a great importance for the achievement of sustainable development [28]. The work of [29][30][31] concluded that CP practices lead to relevant economic and environmental results. SEs have a focus on production management problems, often disregarding environmental factors, due to the pressure they face for meeting short run objectives, together with the lack of resources [16,32].…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been no explanations as to how these levels might lead to unethical behavior. The following section will discuss the ethical implications of compensation schemes, as well as ethical opinions on existing executive cultures, including instances of how management might Dilemmas (Pathan, Haq, & Morgan, 2022;Przychodzen & Gómez-Bezares, 2021;Santulli, 2022;Zhang & Zhang, 2022).The principal-Agent dilemma has been addressed in compensation packages throughout the previous decade. The Principal Agent dilemma arises when shareholders (principals) and executives have opposing interests (the agents) (Voorn et al, 2019).…”
Section: Current Compensation Levelsmentioning
confidence: 99%
“…A director's title comes with a large income, status, and vital business ties. Although shareholders elect directors to boards of directors, CEOs play a key influence in renominating members to the board and deciding director benefits and pay (Pathan et al, 2022).…”
Section: Ethicalmentioning
confidence: 99%
See 1 more Smart Citation